Use of DC Motor Control in Development of Pipe Welding Technology by Using the GMAW Process for Variation of Welding Nozzle Movement - Toruan, Henry Hasian Lumban; Ginting, Berta Br.; Simanjuntak, Melvin Emil; Pakpahan, Binsar Maruli Tua; Sitorus, M.B.H.; Hutajulu, Elferida; Junaidi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Gas Metal Arc Welding (GMAW) welding technology is a welding method that is widely used in industry. A problem that often occurs is that it is difficult for a welder to control the speed of movement of the welding nozzle, which can affect the quality of the welding results. With welding tools that can control the movement of the welding nozzle, this problem can be overcome and increase the efficiency and productivity of the welding manufacturing process. The method for testing the quality of welding results is analyzed visually using the visual test and penetrant test methods. The use of GMAW welding tools for pipe butt joints using DC motor control to vary the movement of the welding nozzle is effective, making it easier for the welder and good welding results. Good welding results were obtained for setting the welding nozzle movement time in 1.4 seconds and 1 second for one left and right the movement cycle on a pipe joint rotating at a constant speed of 24 rpm. Setting the time for the welding nozzle movement in 0.6 seconds for one cycle of left and right movement produces poor welding in pipe joints that rotate at the same speed.